2015
DOI: 10.1002/rra.2867
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Temperature Thresholds Associated with Fish Community Changes in British Columbia, Canada, to Support Identification of Temperature Sensitive Streams

Abstract: We collected fish samples and measured physical habitat characteristics, including summer stream temperatures, at 156 sites in 50 tributary streams in two sampling areas (Upper Fraser and Thompson Rivers) in British Columbia, Canada. Additional watershed characteristics were derived from GIS coverages of watershed, hydrological and climatic variables. Maximum weekly average temperature (MWAT), computed as an index of summer thermal regime, ranged from 10 to 23°C. High values of MWAT were associated with large,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 66 publications
(112 reference statements)
1
37
0
Order By: Relevance
“…Minnow and stone loach are cold water species inhabiting similar zones than brown trout and having upper values of their temperature ranges near 18°C (20 and 18°C for minnow and loach, respectively, FishBase, 2016). The value of 18°C is close to the community threshold of 19°C identified by Parkinson et al (2016) from fish communities of Canadian streams, separating cold from cool water assemblages. It is also comparable to the maximal temperature threshold of 15.7°C found by Brucet et al (2013) as a major split value to explain fish diversity in European lakes by a regression tree analysis.…”
Section: Water Temperaturesupporting
confidence: 70%
See 1 more Smart Citation
“…Minnow and stone loach are cold water species inhabiting similar zones than brown trout and having upper values of their temperature ranges near 18°C (20 and 18°C for minnow and loach, respectively, FishBase, 2016). The value of 18°C is close to the community threshold of 19°C identified by Parkinson et al (2016) from fish communities of Canadian streams, separating cold from cool water assemblages. It is also comparable to the maximal temperature threshold of 15.7°C found by Brucet et al (2013) as a major split value to explain fish diversity in European lakes by a regression tree analysis.…”
Section: Water Temperaturesupporting
confidence: 70%
“…The existence of community thresholds assumes that several species share similar thresholds because they have the same ecological preferences or they replace each other in environmental gradients. In British Columbia (Canada), community temperature thresholds were derived from the analysis of river fish samples at 156 sites, marking large changes from very cold to cold and eventually cool water species (Parkinson et al, 2016). Another Canadian study showed that lake water acidity reduced fish diversity with a pH threshold between 5 and 5.5 (Tremblay and Richard, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Life in mountain streams (where mean annual temperatures <5°C are common) requires special physiological adaptations (13), so aquatic communities typically have low species richness (14,15). However, those extreme conditions also make mountain streams resistant to nonnative species invasions such that many indigenous communities remain intact even after a century of climate change and the global pandemic of anthropogenic species introductions (16).…”
mentioning
confidence: 99%
“…The Wyoming coolwater range identified in this study is warmer than a transitional zone identified in another headwaters region in British Columbia, which ranged from 12–13°C to 19–20°C in terms of summer MWAT (Parkinson et al. ).…”
Section: Discussionmentioning
confidence: 60%
“…; Parkinson et al. ). Threshold detection approaches include multivariate methods, such as ordination, cluster, and similarity index analyses, or threshold indicator methods (Wehrly et al.…”
Section: Challenges In Thermal Guild Development Using Laboratory‐dermentioning
confidence: 99%